Long-Term Results of Pisiformectomy in a Cohort of 57 Patients - Verhiel, Svenna H. W. L.; Blackburn, Julia; Ritt, Marco J. P. F.; Chen, Neal C. (Journal of Wrist Surgery, 2020)
Background Excision of the pisiform is an infrequently used option for pisotriquetral joint dysfunction when nonoperative treatment is ineffective. This study reviews the patient-reported outcomes of patients treated with pisiformectomy, and furthermore focuses on the complications and the need for and time to revision procedure.Materials and Methods Medical records of 57 patients were manually reviewed and assessed for complications, rate of unplanned reoperations, and type of reoperations. Thirty-seven patients (65%) completed patient-rated outcomes surveys at a median of 10 years after their procedure.Results The complication rate was 13% (n = 7). Ulnar nerve symptoms were noted in three patients. No reoperations were performed after the pisiform excision. Out of the 16 patients who had preoperative symptoms of ulnar nerve compression at the wrist, 10 patients reported that their symptoms had completely resolved after the surgery. The median Quick Disability of Arm, Shoulder and Hand (QuickDASH) score after surgery was 4.5 (2.3–16), median score for pain 0 (interquartile range [IQR]: 0–2), and median score for overall satisfaction 10 (IQR: 8–10).Conclusions Pisiformectomy is a surgery used sparingly in cases with refractory pain associated with arthrosis of the pisotriquetral joint or enthesopathy of the flexor carpi ulnaris/pisiform interface. When utilized in this fashion, patients report limited disability on patient-rated outcome measures, low pain scores, and high satisfaction at mid- to late follow-up.
Keywords: complications; patient-reported outcomes; pisiformectomy; pisiform excision